FOSTERING A CHILD’S SOCIAL ADAPTABILITY WITHIN THE FAMILY - Oripova Nodima Halilovna (Web of Journals Publishing, 2025)
This article explores the methodology of fostering a child’s social adaptability during the family upbringing process. It analyzes the theoretical foundations, methodological approaches, and practical methods for developing a child’s socialization and ability to engage in communication with the surrounding environment. The pedagogical potential of the family, parental educational culture, and psychological and social aspects of the family environment are scientifically examined regarding their impact on the child’s level of adaptability. Moreover, effective methods for developing communicative skills, enhancing emotional intelligence, and encouraging positive behavior in the child’s social life adaptation are recommended. The results have practical significance for improving family education processes and supporting children’s successful integration into social environments.
Keywords: Social adaptability; child development; family upbringing; methodology; parent-child communication; dramatization; constructive conflict; methodological recommendations; pedagogical technologies; emotional intelligence.